Effects of different peripheral fatigue protocol on lower limb biomechanical changes during landing and its impact on the risk of anterior cruciate ligament injury: a systematic review - He, Zhanyang; Sun, Gang; Zhu, Houwei; Ye, Binyong; Zheng, Zhe; He, Xiaolong; Pan, Huiju (Frontiers in Bioengineering and Biotechnology, 2025)
Previous research suggests that although fatigue accumulates during competitions and at season’s end, anterior cruciate ligament (ACL) injuries do not significantly increase, with peripheral fatigue-induced muscle weakness potentially playing a key role. The aim of this study is to systematically review the effects of different peripheral fatigue interventions on biomechanical variables associated with ACL injury risk during landing tasks. A systematic search was conducted in five databases Web of Science, Scopus, PubMed, EBSCO, and Cochrane Library up to September 2024. The evidence classification system was used to grade the evidence on lower limb biomechanical changes. A total of 12 studies, involving 217 participants (105 males, 112 females), were included. These studies examined 9 peripheral fatigue protocols, 14 kinematic variables, and 16 kinetic variables. Among the 14 kinematic variables reviewed, strong evidence indicates increased knee internal rotation angles at peak vertical ground reaction force (vGRF) during landing tasks after the knee flexors and extensors peripheral fatigue protocols (Effect size = 0.24–0.68). For the 16 kinetic variables reviewed, strong evidence only suggests a reduction in peak vGRF during landing tasks after knee flexors and extensors peripheral fatigue protocols (Effect size = 0.12–0.32). In conclusion, we found that only two peripheral fatigue interventions were supported by evidence, while most kinematic and kinetic variables showed conflicting results, underscoring the need for further research. Such improvements will help clarify whether current neuromuscular ACL injury prevention programs need to be adapted to account for the biomechanical changes brought about by peripheral fatigue.Systematic Review Registration:clinicaltrials.gov, identifier CRD42024593839.